PRADUGA TAK BERSALAH DAN PRADUGA BERSALAH DALAM PROSES PENEGAKAN HUKUM PIDANA DI INDONESIA OLEH KEPOLISIAN - Nakamnanu, Manuel Defender (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The presumption of innocence is one of the principles that provides legal protection for suspects and defendants in the process of enforcing criminal law, but there is also a view that states that in the investigation process it would be more appropriate to apply the presumption of guilt, therefore in this paper the author will further examine the application of the presumption of innocence and presumption of guilt in the criminal law enforcement process in Indonesia by the Police. To answer these problems, the author uses the research method of library research, namely research that utilizes library sources to obtain data in a study. The method of approach is conceptual (conceptual approach) by studying the principles, theories, doctrines, and principles related to the presumption of innocence and the presumption of innocence, and from the results of the research the author concludes that the presumption of innocence must actually be applied in the examination process at the investigation level.